PERILAKU SPIRITUAL PADA REMAJA YANG MENGALAMI CYBERBULLYING - Dyah Rivani; Sesanti Amiasih; Laili Nur Hidayati (AKPER Pemkab Purworejo, 2022)
Instilling spirituality in a strong family can encourage adolescents to behave positively, this has the opposite effect if low spirituality will cause adolescents to always think negatively so that adolescents can behave in cyberbullying. Using a descriptive correlation research approach, this study attempts to assess the impact of spiritual conduct on cyberbullying behavior in 92 high school adolescents. Questionnaires on cyberbullying and spirituality were used to obtain data. Analysis of the data using the Spearman’s Rho correlation test. These results may differ from many previous studies. The results of this study indicate that cyberbullying behavior is mostly in the low category (91.30%) and spiritual behavior is mostly in the good category (89.13%). This research reveals that there is no influence between spiritual behavior on cyberbullying behavior in adolescents. These results may differ from many previous studies. Although the spiritual behavior in this group shows a good category, their cyberbullying behavior needs to be considering the many stressors that adolescents may face.